Deterministic phase slips in mesoscopic superconducting rings - I. Petković (Nature Portfolio, 2016)
Understanding the decay of persistent current in superconducting rings remains obscure. Here, the authors show detailed agreement between measurements of the persistent current in isolated flux-biased rings and Ginzburg-Landau theory over a wide range of parameters, providing a quantitative picture of the free energy landscape.